Guerra fiscal: validade jurídica da glosa de créditos de ICMS - SEFER, Tiago Nasser (Universidade Federal do Pará, 2017)
The dissertation focuses on the ICMS tax war, which is a phenomenon in which the states seek to attract companies to its territory through tax breaks. To grant ICMS tax break is required unanimous consent of the States under the CONFAZ, which is very difficult. Thus, it has become common that when an irregular incentive is granted for certain companies by a state of origin, the state of destination does not recognize the ICMS credits generated, based on Article 8, I from the Supplementary Law 24/1975. The majority doctrine has been pacified towards being against this non-recognition, and the Supreme Court doesn’t have yet a definitive position on the issue. The text proposal is to build a sound doctrine that opposes the majority and defends the possibility of disallowance of ICMS credits arising from unconstitutional tax breaks. We discuss issues such as rule of law, validity, fiscal federalism, taxpayer fundamental rights, rule incidence matrix, tax liability, non-cumulative system, ICMS, and disallowance of credits. After using the subsidies provided, we hold our thesis as to authorizing the act of credit cancelation.